Anxiety, Depression, and Stress Are Associated With Internet Gaming Disorder During COVID-19: Fear of Missing Out as a Mediator - Wang, Yang; Liu, Bingjie; Zhang, Lei; Zhang, Peng (Frontiers in Psychiatry, 2022)
Background Many teenagers suffered negative emotional states, especially anxiety and depression, during the COVID-19 outbreak, and most teenagers choose Internet games to cope with negative emotion. Previous evidence indicated that fear of missing out is related with anxiety and depression in teenagers with Internet gaming disorder, but it is unclear how fear of missing out influences depression, anxiety, or stress. Methods Based on an I-PACE model, using Depression, Anxiety, Stress Scale (DASS-21), Fear of Missing Out Scale, and Internet Gaming Addiction Scale, and 324 middle school students as participants, this study explored the mediating effect of fear of missing out on depression, anxiety, or stress and Internet gaming disorder. Results The results showed that depression and stress are significantly related to Internet gaming disorder through the partial mediating of fear of missing out. Anxiety is not significantly related to Internet gaming disorder through the full mediating of fear of missing out, and anxiety and stress have a greater predictive effect on Internet gaming disorder through fear of missing out. Results also demonstrated that students who play Honor of Kings or Player Unknown's Battlegrounds have more risk to develop Internet gaming disorder. Conclusions The results indicated that fear of missing out as a mediator regulates the relationship among depression, anxiety, and stress and Internet game disorder. Specifically, under the mediation of fear of missing out, teenagers with anxiety are more likely to develop Internet gaming disorder, while teenagers with depression or stress might be prone to other types of Internet use disorders.